Profile of Medication Variations and Dose Adjustment to Diabetes Mellitus Patients Response in PKU Muhammadiyah Hospital dan Panti Rapih Hospital period OctoberDecember 2014 - Imaniar Noor Faridah; Dyah Aryani Perwitasari; Desty Kusumaningsih; Riana Prastiwi Handayani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Diabetes mellitus patients may have a different response tosimilar medication. Therefore, individualized treatment and monitoringof the therapy is needed to ensure the patients’ response. Alternativemedication or dose adjustment should be considered in order to achievethe therapeutic goal.Objective: The aim of this study was to find out patients’ response tomedication variation or dose adjustment.Methods: This study used descriptive design in PKU MuhammadiyahHospital and Panti Rapih hospital period October-December 2014.Participants are all patients who got pharmacological therapy for treatmentof diabetes mellitus type 2, including oral antidiabetics and/ insulin andmet the inclusion criteria. The response of therapy was checked 2 times,during check-in and check-out.Results: Analysis of response variation showed that individualizedresponse existed, in which positive response occurred in 10 patients andthe other had a negative response. The changes were dose adjustmentand medication alteration or medication addition. From 6 patients whoneeded medication adjusment, 5 patients had a positive response, andothers had a negative response. Whereas from 6 patients whose dosage ormedication was not changed, 5 of them had a positive response while onehad a negative response.Conclusion: Individualized treatment is needed to achieve a therapeuticgoal. Individualized treatment can be done through dose adjustment andmedication alteration, or medications addition.